أثر الاستقرار السياسي على السياحة والسفر في الدول الأوروبية – دراسة حالة الحرب الروسية الأوكرانية -: The impact of political stability on tourism and travel in European countries - A case study of the Russian-Ukrainian war - - زيان بروجة علي (Journal of North African Economies, 2025)
This study aims to demonstrate the impact and importance of political stability on tourism and travel in European countries by examining the case of the Russian-Ukrainian war, which began at the end of February of the current year, and which its effects have been reflected on international tourism demand in many countries of the world, especially on both the countries neighbouring the territory of the political event location and the conflict parties. This study reached many results, the most important is that the travel and tourism sector recorded negative indicators in both Russia and Ukraine, especially in the latter, in which flights have been almost completely interrupted, while in the former, the sanctions imposed by the European Union on Russian airlines and banning them from flying in its airspace, led to a decline in Russian air transport services, and contributed to the transformation of international tourist destinations for Russian tourists towards non-European tourist destinations.